Download presentation
Presentation is loading. Please wait.
Published byAbigayle Yarnall Modified over 9 years ago
1
Introduction Functions are relations in which each element in the domain is mapped to exactly one element in the range; that is, for every value of x, there is exactly one value of y. In order to understand how functions are related, we need to understand how to perform different arithmetic operations on functions. In this lesson, we will add, subtract, multiply, and divide exponential and linear functions. 1 3.7.1: Operating on Functions
2
Key Concepts Combine linear and exponential expressions using addition: (f + g)(x) = f(x) + g(x). In other words, add the two functions together by combining like terms. Combine linear and exponential expressions using subtraction: (f – g)(x) = f(x) – g(x). In other words, subtract the second function from the first while making sure to distribute the negative across all terms of the second function. 2 3.7.1: Operating on Functions
3
Key Concepts, continued Combine linear and exponential expressions using multiplication: (f g)(x) = f(x) g(x). In other words, multiply the two functions together. Combine linear and exponential expressions using division: (f ÷ g)(x) = f(x) ÷ g(x). In other words, divide the first function by the second function. Use a fraction bar to display the final function. 3 3.7.1: Operating on Functions
4
Common Errors/Misconceptions incorrectly using the distributive property when subtracting two expressions incorrectly using the order of operations when multiplying or dividing two expressions incorrectly using the distributive property when multiplying two expressions 4 3.7.1: Operating on Functions
5
Guided Practice Example 1 If f(x) = 3x + 2 and g(x) = 2x – 7, what is the result of adding the two functions? What is (f + g)(x)? How do you represent this algebraically? 5 3.7.1: Operating on Functions
6
Guided Practice: Example 1, continued 1.Add the two function rules. (f + g)(x) = f(x) + g(x) Since f(x) = 3x + 2 and g(x) = 2x – 7, (f + g)(x) = (3x + 2) + (2x – 7). 6 3.7.1: Operating on Functions
7
Guided Practice: Example 1, continued 2.Combine like terms. Clear the parentheses and reorder the terms on the right side of the equation. (f + g)(x) = (3x + 2) + (2x – 7)Equation (f + g)(x) = 3x + 2 + 2x – 7Remove the parentheses. (f + g)(x) = 3x + 2x + 2 – 7Reorder the terms: variables with coefficients first, followed by constants. 7 3.7.1: Operating on Functions
8
Guided Practice: Example 1, continued 3.Simplify the equation. (f + g)(x) = 3x + 2x + 2 – 7Equation (f + g)(x) = 5x – 5 The result of adding f(x) = 3x + 2 and g(x) = 2x – 7 is (f + g)(x) = 5x – 5. 8 3.7.1: Operating on Functions ✔
9
9 Guided Practice: Example 1, continued 9
10
Guided Practice Example 3 If f(x) = 2x – 3 and g(x) = 4x – 11, what is the result of subtracting the two functions? What is (f – g)(x)? How do you represent this algebraically? 10 3.7.1: Operating on Functions
11
Guided Practice: Example 3, continued 1.Subtract the two function rules. (f – g)(x) = f(x) – g(x) Since f(x) = 2x – 3 and g(x) = 4x – 11, (f – g)(x) = (2x – 3) – (4x – 11). 11 3.7.1: Operating on Functions
12
Guided Practice: Example 3, continued 2.Combine like terms. Clear the parentheses and reorder the terms on the right side of the equation. Be careful to correctly distribute the negative sign. (f – g)(x) = (2x – 3) – (4x – 11) Equation (f – g)(x) = 2x – 3 – 4x + 11 Distribute the negative. (f – g)(x) = 2x – 4x – 3 + 11 Reorder the terms: variables with coefficients first, followed by constants. 12 3.7.1: Operating on Functions
13
Guided Practice: Example 3, continued 3.Simplify the equation. (f – g)(x) = 2x – 4x – 3 + 11Equation (f – g)(x) = –2x + 8 (f – g)(x) = –2x + 8 is the result of subtracting f(x) = 2x – 3 and g(x) = 4x – 11. 13 3.7.1: Operating on Functions ✔
14
14 3.7.1: Operating on Functions Guided Practice: Example 3, continued
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.